Profil Awal Kemampuan Representasi Ilmiah Calon Guru Fisika pada Pembelajaran Fisika Modern - Mulhayatiah, Diah; Sinaga, Parlindungan; Rusdiana, Dadi; Kaniawati, Ida; Putri, Nurhalia Maulida (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2022)
This research was conducted with the aim of determining the ability to learn physics in physics education students in solving physics problems using various types of representation modes. This research was conducted using descriptive qualitative approach. A descriptive qualitative approach was carried out by conducting literature studies in previous research journals to support the validity of this research. The results showed that physics education students are easier to solve problems about modern physics by using the image and graph representation mode than other representation modes